Politics of place: The meaningfulness of resisting places. (February 2017) - Courpasson, David; Dany, Françoise; Delbridge, Rick
The meaningfulness of the physical place within which resistance is nurtured and enacted has not been carefully considered in research on space and organizations. In this article, we offer two stories of middle managers developing resistance to managerial policies and decisions. We show that the appropriation and reconstruction of specific places by middle managers helps them to build autonomous resisting work thanks to the meanings that resisters attribute to the place in which they undertake resistance. We contribute to the literature on space and organizations by showing that resistance is a social experience through which individuals shape physical places and exploit the geographical blurring of organizations to develop political efforts that can be consequential. We also suggest the central role played by middle managers in the subversion of these meaningful places of resistance.